Dyktat testocentryzmu w polityce edukacyjnej. Refleksje na marginesie książki Marka Piotrowskiego Od TQM do „żandarma”, czyli pod prąd - Bielecki, Piotr (Wydawnictwo Naukowe UAM, 2015)
The book is an adequate and novel response to the continually growing interest both in the effectiveness of the external evaluation of schools and students and in the improved quality of common education. Analyses of the data derived from an empirical research conducted by the Author of the book reviewed do not support the proposition that external standardized tests, given the reality of Poland’s schooling system, are appropriate and satisfactory (fair and objective) measures of students’ academic achievements. Moreover, a similarly poor effect has been observed in the field of continuous quality improvement. Research evidence provided by the Author reveals the high importance (also social) and complexity of the negative consequences of standardized high-stake testing. Bearing that in mind, the Author of the book addresses the issue of changing the so called “social paradigms” in education policy and schooling, that is a shift from “classic”, old-established patterns of teaching and testing to application of principles and tools of TQM. This primary claim constitutes THE correct base for considering current and future numerous initiatives for the sake of common education improvement. Owing to the positive final evaluation of the value of the topic, the major results of the study, the Author’s generalizations and conclusions, and the overall scientific contribution, the review notes are generally complimentary. Though largely favorable, the review contains some significant criticisms and items of concern (shortcomings and omissions) with regard to the research aims and objectives of the book, its range, contents, structure, style of writing, arguments used, theoretical approach, methods employed, and the literature used. Comments on some of the limitations of the book, especially related to its theoretical background, methodology and content of the study, provided the reviewer with the opportunity for a more critical discussion highlighting the topics in question.
The Dictate of Test-orientation in Education Policy. Reflections on Marek Piotrowski’s Book From TQM to “Gendarme”, i.e. Against the Mainstream
Keywords: education policy; education quality; TQM; standardized tests